KEPEMIMPINAN PENDIDIKAN DI ERA 5.0 DALAM KURIKULUM MERDEKA - Mahmuda; Edi Yulianto; Nina Oktarina; Fathur Rokhman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The 5.0 era is marked by the integration of advanced technology in everyday life, including in the field of education. The concept of the Independent Curriculum gives educational institutions the freedom to develop a curriculum according to student needs and local contexts. This article discusses the role of educational leadership in the implementation of the Independent Curriculum in the 5.0 era, as well as the challenges and strategies that can be applied to achieve effective educational goals in the context of the Independent Curriculum in the 5.0 era, which is marked by the integration of advanced technology and a more flexible learning approach. This study aims to identify the challenges and opportunities faced by educational leaders in implementing the Independent Curriculum and the strategies that can be used to improve teaching effectiveness. The methods used are literature studies and interviews with principals and teachers in several educational institutions. The results of the study indicate that visionary and collaborative leadership are essential in creating an innovative learning environment. In addition, ongoing training for teachers and the development of a collaborative culture among educators are the keys to successful curriculum implementation. The conclusion of this study emphasizes that educational leadership that is adaptive and responsive to technological changes and student needs can improve the quality of education in the 5.0 era.